Sex-specific behavioral changes in middle-aged mice - Nanbin Lou; Yibin Zhu; Xiaohui Du; Luyang Wang; Haojie Tang; Sinan Hu; Ruopeng Xiao; Yiwen Wang; Ke Fang; Shanshan Li; Chunhui Yuan; Weiyun Li; et al. (Scientific Reports)
Abstract Aging is known to cause significant changes in cognition, motor functions, emotional stability, and social behaviors. While research has documented age-related declines in these domains, there is a gap in understanding how aging affects middle-aged individuals, particularly in terms of sex differences. This study aims to fill this gap by examining behavioral changes in middle-aged mice compared to young adult mice, focusing on motor functions, anxiety-like behavior, recognition memory, and social behavior, and exploring sex differences in these domains. We utilized a series of behavioral tests in mice, including the open-field test for motor function, the elevated O-maze for anxiety-like behavior, the novel-object recognition test and Y-maze for cognitive performance, and the three-chamber sociability test for social behavior. Our findings revealed that both sexes presented increased anxiety-like behavior and impaired spatial recognition memory during middle age compared to young adult mice. However, middle-aged female mice presented unique behavioral deficits, including reduced locomotor activity, a marked decline in nonspatial recognition memory, and disrupted social novelty preference. These differences highlight the distinct vulnerability of female mice compared with their male counterparts. Understanding these differences is crucial for predicting later changes and enabling earlier interventions, contributing to a more comprehensive view of brain aging and its associated behaviors.